Mind the gap: DNA barcoding on Pachygrapsus crabs - Cátia Alves; Lara Baptista; Patrícia Madeira; Nuno Vaz Álvaro; António Santos; Harald Meimberg; Sérgio P. Ávila; Manuel Curto (Metabarcoding and Metagenomics, 2025)
DNA barcode databases for marine invertebrates faces significant challenges, with several species revealing taxonomic issues like misidentification, ambiguity or shared barcodes. This highlights the importance of the availability of robust genetic data to resolve taxonomic uncertainties and improve species identification, which in many groups of invertebrates, like crustaceans, is lacking. Based on molecular data from the Cytochrome c oxidase I 5′ gene region (COI) for barcoding, this study highlights some of these challenges by addressing existing taxonomic ambiguities and highlighting the scarcity of genetic data for several of the shore crab genus Pachygrapsus Randall, 1840. As expected, molecular data availability is highly skewed towards taxa more prevalent in the Northern Hemisphere. Our analysis reveals a clear barcoding gap amongst Pachygrapsus species, with average interspecific p-distances of 18.75%, exceeding previously reported values for crustaceans. Furthermore, high intraspecific variation (0.70% average) suggests potential taxonomic issues, particularly within P. gracilis (de Saussure, 1857). East and west Atlantic P. gracilis populations exhibit substantial divergence (3.6% p-distance), raising the possibility of ongoing speciation due to limited gene flow across the Atlantic Ocean. Similarly, populations of P. crassipes in the east and west North Pacific exhibit substantial divergence (3.3% p-distance), which suggests possibly another speciation process. COI barcoding proves effective for species identification within Pachygrapsus and in unravelling intraspecific patterns indicative of cryptic diversity guiding further taxonomic revisions integrating morphological, genetic and ecological data.